Environmental regulation and corporate green innovation performance: A study on the relationship between technological innovation and green innovation performance - Wang, Lan; Mat, Tuan Zainun Tuan; Abdullah, Azizah (Edelweiss Applied Science and Technology, 2025)
Green innovation is the key to achieving a win-win situation between economic development and environmental protection, involving areas such as energy conservation, resource recycling, and pollution control. It helps reduce environmental costs for enterprises, enhance competitiveness, and promote industrial upgrading. Studying the impact of environmental regulations on green innovation in enterprises is of great significance for reality. This article delves into the relationship between technological innovation and corporate green innovation performance under the background of environmental regulation. By reviewing relevant literature on Scopus, Web of Science, ScienceDirect, SpringerLink, Wiley, and SAGE, it elucidates the internal mechanism by which technological innovation promotes the improvement of green innovation performance, analyzes the moderating effect of environmental regulation on the relationship between the two, and looks forward to future research directions, aiming to provide theoretical references for enterprises to achieve green innovation development under environmental regulation. In the face of constantly changing market and competitive environments, technological innovation helps enterprises enhance their dynamic capabilities, enabling them to quickly adapt to environmental changes, seize opportunities for green innovation, and thereby improve green innovation performance.